Avaliação da via do Hedgehog nas hepatites crônicas B e C : da fibrose zero até a cirrose associada ou não ao carcinoma hepatocelular - Pereira, Thiago de Almeida (2010)
Hedgehog (Hh) pathway activation promotes many processes that occur during fibrogenic liver repair. Whether the Hh pathway modulates the outcomes of virally-mediated liver injury has never been examined. Gene-profiling studies of human hepatocellular carcinomas (HCC) demonstrate Hh pathway activation in HCCs related to chronic infection with hepatitis B virus (HBV) or hepatitis C virus (HCV). Because most HCC develop in cirrhotic livers, we hypothesized that Hh pathway activation occurs during fibrogenic repair of liver damage due to chronic viral hepatitis, and that Hh-responsive cells mediate disease progression and hepatocarcinogenesis in chronic viral hepatitis. Methods Immunohistochemistry and qRT-PCR analysis were used to analyze Hh pathway activation and identify Hhresponsive cell types in archival liver biopsies from 45 patients with chronic HBV or HCV with different stages of fibrosis (F0-4), some of which also presented HCC. Hh signaling was manipulated with cyclopamine in primary human hepatic stellate cells (HSC) and sinusoidal endothelial cells (SEC). Angiogenesis assay was used to investigate if the pathway plays a role in tube formation. SECs were incubated with recombinant Shh, conditioned media from HSC, cyclopamine, short hairpin RNA against smoothened or their respective controls and the length of vascular tubes were measured by morphometry. Hedgehog production was investigated in Huh7 cells infected with JFH-1 and in a rat hepatoma cell line that express the HBV X gene by qRT-PCR. Results We found increased hepatic expression of Hh ligands (Shh and Ihh) in all patients with chronic viral hepatitis (p<0.005), and demonstrated that infection with JFH-1 or ectopic expression of the HBV X gene stimulated cultured hepatocytes to produce Shh (p<0.005). The major cell populations that expanded during cirrhosis and HCC (i.e., liver myofibroblasts, activated endothelial cells, and progenitors expressing markers of tumor stem/initiating cells Krt7, CD133, Epcam and survivin) were Hh-responsive (Patched and Gli-2 positive) and higher levels of Hh pathway activity associated with cirrhosis and HCC (p<0.005). Inhibiting pathway activity in Hh-responsive target cells (HSC and SEC) reduced fibrogenesis (p<0.005 for αSMA and p<0.05 for col1α1 expression) and angiogenesis (p<0.05). Conclusions HBV/HCV infection increases hepatocyte production of Hh ligands in hepatocytes and expands types of Hh-responsive cells, including myofibroblasts and xiv sinusoidal endothelial cells that associate with fibrosis progression to cirrhosis and hepatocellular carcinoma. Moreover, hedgehog-responsive progenitors that are undergoing epithelial-to-mesenchymal transition accumulate during the progression of viral hepatitis and may play a role in the development or progression of hepatocellular carcinoma. In vitro inhibition of Hh-signaling in primary human hepatic stellate cells and sinusoidal endothelial cells suggest the possibility of using Hh inhibitors as potential tools to prevent cirrhosis and hepatocellular carcinoma in patients with chronic hepatitis B and C.